Perbedaan Kuantitas Lakrimal Sebelum dan Sesudah menggunakan Komputer pada Pekerja PT. Bank Syariah Indonesia Kota Lhokseumawe menggunakan Uji Schirmer I - Aqsha Madina; Nora Maulina; Muhammad Sayuti (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The use of computers continues to increase over time and has become a daily necessity. In line with this, dry eye complaints often arise from workers who use computers. The decrease in the production of tear secretion is closely related to the use of computers for a long time, where the longer the duration of use, the lower the frequency of blinking which results in an increase in tear evaporation, so the eyes will become dry and uncomfortable. This study intends to see the difference in lacrimal quantity before and after using the computer at PT. Indonesian Islamic Bank in Lhokseumawe City. The method used in this study is a quasi-experimental (quasi-experimental) research design in the form of a pretest-posttest control one group design and uses primary data taken through the examination of the Schirmer I test to 31 respondents. The results showed that 22 respondents (71%) had decreased tear secretion, 2 respondents (6.5%) had increased secretions, and 7 respondents (22.6%) had constant secretions. Statistical analysis using the Wilcoxon alternative test with the results obtained a significant value of 0.002 (p<0.05), so statistically there is a statistically significant difference in the mean of tear secretion with the Schirmer I test in PT. Indonesian Islamic Bank in Lhokseumawe City. The conclusion of this study is that there are differences in the quantity of lacrimal before and after using the computer at PT. Bank Syariah Indonesia in Lhokseumawe City uses the Schirmer I . test.